HOW GDPR TREATS AUTOMATED DECISION-MAKING: HOW GDPR TREATS AUTOMATED DECISION-MAKING - Simeonova, Iliana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This article examines how the General Data Protection Regulation (GDPR) regulates automated decision-making, including profiling, in the context of personal data processing. It analyzes the main provisions of Article 22 of the Regulation, as well as the conditions under which fully automated decisions that produce legal effects or significantly affect data subjects are permitted. The article highlights the rights of data subjects – the right to human intervention, the right to express their point of view, and the right to contest the decision – along with the responsibilities of data controllers. Practical examples and commentary are included, focusing on the application of these rules in the context of modern technologies such as algorithmic profiling, artificial intelligence, and machine learning.